Greywater Waste Treatment as a Solution to the Clean Water Crisis in Bontang City - Lies Kurniawati Wulandari (Universitas Tribhuwana Tunggadewi Malang, 2022)
This research develops a technique for treating greywater and rainwater wastewater into clean water, namely by using a filtration technique using sand as a filter material, as well as adding PAC (Poly Aluminum Chloride) and soda ash (Sodium Chloride) to neutralize pH. Observations were made on variations in PAC and soda ash levels (X1) and variations in sand thickness (X2) on water quality parameters (Y) consisting of pH and turbidity (NTU). Data analysis was performed using the linear regression method. The treatment techniques applied are proven capable of converting greywater and rainwater waste into class II clean water. In other words, water can be used for daily needs but not for consumption. The filtration method can remove pollutants in greywater wastewater and be a solution for meeting clean water in urban areas, especially in Bontang City, East Kalimantan.ABSTRAKPenelitian ini mengembangkan sebuah teknik pengolahan air limbah greywater dan air hujan menjadi air bersih, yakni dengan teknik filtrasi menggunakan pasir sebagai material filter, serta penambahan PAC (Poly Alumunium Chloride) dan soda ash (Sodium Chloride) untuk menetralisir pH. Pengamatan dilakukan terhadap variabel variasi kadar PAC dan soda ash (X1) dan variasi ketebalan pasir (X2) terhadap parameter kualitas air (Y) yang terdiri dari pH dan kekeruhan (NTU). Analisis data dilakukan dengan menggunakan metode regresi linier. Secara umum, teknik pengolahan yang diterapkan terbukti mampu merubah limbah greywater dan air hujan menjadi air bersih kelas II. Dengan kata lain, air telah dapat digunakan untuk keperluan sehari-hari, namun tidak untuk dikonsumsi. Metode filtrasi mampu menghilangkan polutan yang terkandung dalam air limbah greywater, dan dapat menjadi solusi pemenuhan air bersih di kawasan perkotaan, khususnya Kota Bontang, Kalimantan Timur.